Effects of Myristica fragrans Houtt. (nutmeg) extract on chemical characteristic of raw beef during frozen storage - Zakaria, M. P. M.; Abas, Faridah; Rukayadi, Yaya (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2015)
The objective of this study was to investigate the effect of nutmeg (Myristica fragrans Houtt.) extract at different concentrations on chemical characteristics of raw beef under frozen storage. Nutmeg extracts at concentrations of 0.25%, 0.65%, 1.25%, 2.50% and 5.00% (g/ml) were used to treat raw beef (2.5 × 2.5 × 1.0 cm; 4 ± 0.5 g) with dilution method. Treated samples were then individually packed in overwrapped trays and stored for 3 weeks at -18 ± 1°C. The effects of the extract on the chemical characteristics such as lipid oxidation, colour, pH, moisture, fat, and protein content of raw beef were evaluated at 0, 4, 7, 10, 14 and 21 days of storage. Lipid oxidation was evaluated based on thiobarbituric acid-reactive substance (TBARS) content. Colour of beef was observed by spectrophotometer in colorimetic parameters CIELabs. Values of pH were measured using pH meter. Moisture, fat and protein content were determined using method by Analysis Association of Official Analytical Chemists (AOAC). The result showed that extract at concentration of 1.25% inhibited TBARS value meaning that extract of 1.25% or more was able to maintain the oxidative stability of beef at -18°C. A 1.25% of extract was also able to maintain the redness (a*) of treated beef compared to untreated during frozen storage. The pH values of all samples beef decreased starting from 10th day of storage. Untreated samples (0.00%) showed the lowest pH values compared to other treated samples at the end day of storage. There was no significant different in term of protein content in all treated or untreated samples. However, fat and moisture content were significantly affected by the concentration of nutmeg extract. Treated beef was able to retain its moisture with only loss of moisture ranging from 0.2% - 2.00% while untreated samples had 5.00% loss of moisture. The fat content of untreated samples (0.00%) showed a reduction of 0.2% of fat content at the end of storage compared to all treated sample with only loss of 0.1% - 0.05%. Overall, nutmeg extract can be used to maintain the chemical characteristics of raw beef during storage for 3 weeks.